Atypical enteropathogenic escherichia coli as aetiologic agents of sporadic and outbreakassociated diarrhoea in Brazil - Vieira, Melissa A. [UNESP]; Dos Santos, Luï¿½s F.; Dias, Regiane C. B. [UNESP]; Camargo, Carlos H.; Pinheiro, Sandra R. S.; Gomes, Tï¿½nia A. T.; Hernandes, Rodrigo T. [UNESP] (Microbiology Society, 2016)
Enteropathogenic Escherichia coli (EPEC) are important agents of diarrhoea in industrialized as well as developing countries, such as Brazil. The hallmark of EPEC pathogenesis is the establishment of attaching and effacing lesions in enterocytes, in which pedestal-like structures are formed underneath adherent bacteria. EPEC are divided into two subgroups, typical (tEPEC) and atypical (aEPEC), based on the presence of the EPEC adherence factor plasmid in tEPEC and its absence in aEPEC. This study was designed to characterize 82 aEPEC isolates obtained from stool samples of diarrhoeic patients during 2012 and 2013 in Brazil. The majority of the aEPEC were assigned to the phylo-group B1 (48.8 %), and intimin subtypes θ (20.7 %), β1 (9.7 %) and λ (9.7 %) were the most prevalent among the isolates. The nleB and nleE genes were concomitantly detected in 32.9%of the isolates, demonstrating the occurrence of the pathogenicity island O122 among them. The O157-plasmid genes (ehxA and/or espP) were detected in 7.3%of the isolates, suggesting that some aEPEC could be derived from Shiga-toxin-producing E. coli that lost the stx genes while trafficking in the host. PFGE of 14 aEPEC of serotypes O2: H16, O33: H34, O39: H9, O108:H– and ONT: H19 isolated from five distinct outbreaks showed serotype-specific PFGE clusters, indicating a high degree of similarity among the isolates from the same event, thus highlighting these serotypes as potential aetiologic agents of diarrhoeal outbreaks in Brazil.